International Nuclear Information System (INIS): Malaysia’s contribution for nuclear knowledge preservation - Yusof, Mohd Hafizal; Hassan, Mohd Hasnor; Adnan, Habibah; Ali, Iberahim (2012)
International Atomic Energy Agency (IAEA) is an organization under the United Nations (UN), which serves to disseminate accurate information about the nuclear matters.In accordance with its role, an International Nuclear Information System (INIS) was established in 1970 to provide opportunities for member countries under the auspices of the IAEA to share information, expertise and knowledge, particularly in the nuclear field. Malaysia became a member since 1978, and the first country's input was posted in 1980. INIS activities are supervised by liaison officers (LO) to monitor and oversee matters relating to INIS management. INIS has developed 49 subject matters (subject heading) and LO needs to prepare, review and compile the records before sending to INIS database at IAEA headquarters in Vienna, Austria. Material received will be processed before distributing to all IAEA member states through INIS website or CD to countries that subscribe to it.This paper focused on how Malaysia contributes to development of INIS and to promote Malaysian about the existence of this database that not only focused on nuclear science but also related technologies.